Future Apparel Buying Intention: Mediating Effect of Past Apparel Buying Behaviour and Past Apparel Buying Experience. Issue 3 (June 2018) - Krishnakumar, M.
Apparel buying behaviour is influenced by various factors like consumer attitude, store attributes, external factors, product attributes, etc. Besides, factors like the past apparel buying behaviour of the consumers and the past apparel buying experience may also have significant influence in the future apparel buying intention of apparel. This study aims at the effect of various factors on future apparel buying intention and also the mediating effect of past apparel buying behaviour and past apparel buying experience on future apparel buying intention. The results showed that there were partial mediating effects of past apparel buying behaviour and past apparel buying experience on future apparel buying intention. Based on the findings, managerial implications have been suggested for the apparel retailers.